Cute Creatures to Knit and Crochet - Search Press Limited (USA Search Pr Ltd, 2011)
A delight for all ages, these cuddly creature inspirations are ideal for those wishing to knit or crochet gifts for their children, grandchildren, friends, colleagues, or even themselves. The projects vary in size from a tiny crocheted piglet keychain and a lovable hippopotamus to a flamboyant chicken called Antoinette and even the fantastical "Martian dog," forming a menagerie that contains something for everyone. Step-by-step instructions, helpful photographs, and practical charts are also included
Paperback
2
Keywords: Crafts & hobbies; Needlework -- crocheting; Needlework -- knitting